Reestructuración pedagógica en base a la modalidad de los CIBV del Centro de Educación Inicial “Los Pequeños Querubines” de la comunidad Llactayo San Isidro de la parroquia Tanicuch , Provincia de Cotopaxi. - Sandoval Espín, Ruth Elizabeth (2015)
As part of the actions being undertaken by the State has structured a series of programs and modalities between these we have the creation of the Children's Centers of Good Living. The work presented below, part of the research and analysis of the current situation at the Center for Early Education "Little Cherubs" located in San Isidro Llactayo parish Tanicuchi province of Cotopaxi community and aims to determining the problems faced in terms of the quality of educational services and provide solutions to it. In this context it is determined that the community mostly rejects initial education and prefer family care for their children. As part of the problem there is an estrangement between the staff working in the unit care and parents, inadequate staff profile, shortage of teaching materials, little knowledge of the policies of the technical standard of comprehensive child development governing mode the CIBV. Furthermore, it should be stressed that participatory research and direct observation has been a mainstay in this activity because that from the community experience with local stakeholders has been obtained result in involvement in which there is openness to what Initial concerns Education. Using different methods such as interactive workshop with parents and staff survey who serves in the children's center of good living.